1981
DOI: 10.1021/bi00510a023
|View full text |Cite
|
Sign up to set email alerts
|

Differences in iron-fluoride bonding between the isolated subunits of human methemoglobin fluoride and sperm whale metmyoglobin fluoride as measured by resonance Raman spectroscopy

Abstract: The heme geometries of the isolated alpha and beta subunits of human methemoglobin fluoride (HbIIIF) and sperm whale metmyoglobin fluoride (MbIIIF) have been examined by exciting their Raman spectra within their ca. 6000-A charge-transfer absorption bands. The Fe-F stretching vibration at 471 cm-1 in the beta subunits shifts to 466 cm-1 in the alpha subunits and to 461 cm-1 in MbIIIF. The Fe-F bond is estimated to elongate by 0.02 A in the alpha subunits and 0.03 AZ in MbIIIF compared with that in the beta sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Assignment of the ν­(Fe–F) bands at 385, 390, and 393 cm –1 for the Kp Cld–F, Da Cld–F, and Da Cld­(W227F)–F complexes, respectively, was facilitated by Raman excitation within both the Soret and CT2 transitions using 406.7 and 441.6 nm light, respectively. Resonance enhancement of scattering by the z -polarized ν­(Fe–F) modes of heme fluorides has been reported with excitation at the frequency of the x , y -polarized CT1 transition, where scattering by ν­(Fe–F) gains resonance enhancement in hemes exhibiting equilibrium out-of-plane distortion . More recently, scattering by the ν­(Fe–F) modes has been achieved via excitation within the z -polarized CT2 transition, whose energy lies between those of the B and Q­(0,1) transitions (Figure , insets) .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Assignment of the ν­(Fe–F) bands at 385, 390, and 393 cm –1 for the Kp Cld–F, Da Cld–F, and Da Cld­(W227F)–F complexes, respectively, was facilitated by Raman excitation within both the Soret and CT2 transitions using 406.7 and 441.6 nm light, respectively. Resonance enhancement of scattering by the z -polarized ν­(Fe–F) modes of heme fluorides has been reported with excitation at the frequency of the x , y -polarized CT1 transition, where scattering by ν­(Fe–F) gains resonance enhancement in hemes exhibiting equilibrium out-of-plane distortion . More recently, scattering by the ν­(Fe–F) modes has been achieved via excitation within the z -polarized CT2 transition, whose energy lies between those of the B and Q­(0,1) transitions (Figure , insets) .…”
Section: Resultsmentioning
confidence: 95%
“…As ν(Fe−F) modes have been shown to be isolated (i.e. they behave as diatomic oscillators 45 ), the compositions of the other normal heme modes are sufficiently unperurbed by F − binding that they are easily correlated between the spectra recorded in the absence and presence of F − . Finally, by moving the exciting wavelength away from the B band and toward or within the z -polarized CT2 absorbance band, the z -polarized ν(Fe−F) band gains resonance enhancement while the relative intensities of the in-plane polarized heme bands are diminished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 The peaks centered at 375 and 580 cm À1 were assigned to Fe-Cl and Fe-N 45 vibrations, respectively. The appearance of two new peaks after adsorption at 485 and 533.5 cm À1 associated with Fe-F vibrations 46 indicated that complexation between Fe and F ions occurred. However, observation of any notable change in the intensity of the Fe-Cl peak was difficult possibly because only a small amount of Cl and F ions was exchanged in the 10 mg L À1 fluoride solution.…”
Section: Pccp Papermentioning
confidence: 98%
“…Band 5 as well as band 7 arise from vibrational modes closely associated with the core of the heme (see Table 1) and they have been shown to be markers for the heme macrocycle structure. Asher and Schuster (30) found a correlation between a frequency shift from 1,232 to 1,217 cm Ϫ1 and a decreased heme core size as well as an out-of-plane movement of the iron toward the proximal histidine, for the hemes of ␣ and ␤ hemoglobin subunits in Raman measurements. Berthomieu et al (32) showed that upon oxidation a band shift from 1,237 to 1,223 cm Ϫ1 occurred in IR-absorption spectra of double-coordinated Fe-protoporphyrin IX.…”
mentioning
confidence: 97%